A Case of a Bilateral Cicatricial Upper Eyelid Entropion After Hematopoietic Stem Cell Transplantation in Mucopolysaccharidosis Type I. (May 2017) - Dulz, Simon; Wagenfeld, Lars; Richard, Gisbert; Schrum, Johanna; Muschol, Nicole; Keserü, Matthias
Abstract : Minor eyelid abnormalities are commonly encountered in mucopolysaccharidosis, but only rarely leading to a clinically relevant situation. The authors report a clinical case of severe bilateral cicatricial entropion of the upper eyelids, leading to recurrent conjunctival infections, corneal erosion, persistent epiphora, and a major decline in life quality in a 7-year-old boy with mucopolysaccharidosis type I who underwent hematopoietic stem cell transplantation at 1.6 years old. A bilateral anterior lamellar repositioning including eyelid split and cryoepilation was performed to correct bilateral upper eyelid entropium and trichiasis. Three months after the surgical intervention, the patient showed a persistent regular eyelid position with only mild recurrent right-sided lateral upper eyelid entropion. A significant reduction in conjunctival infections and epiphora with complete discontinuation of topical therapy was achieved. Although mucopolysaccaridosis is associated with eyelid abnormalities, the authors conclude that the described case is most likely due to chronic graft versus host disease. Abstract : The rare case of a bilateral cicatricial entropion in a patient with mucopolysaccaridosis Type I and chronic graft-versus-host disease.